A cross-sectional survey on mother-to-child transmission of HIV among the migrant population in Dongguan, China - Pan, Congcong; Pan, Haiyan; Liang, Dongmei; Liu, Yuanyuan; Yin, Sichun; Zhong, Jianbo; He, Songmei (Frontiers in Global Women's Health, 2023)
Background The migrant population, comprising individuals who migrate from rural to urban areas, confronts distinct challenges that heighten their vulnerability to HIV infection. This study systematically gathered and analyzed data from a representative sample of participants, including pregnant women living with HIV and their infants, to elucidate sociodemographic characteristics, HIV testing and treatment profiles, as well as neonate clinical data. The resulting findings offer valuable insights into the specific risk factors and barriers to prevention that the migrant population in Dongguan encounters. These results, in turn, facilitate the development of targeted interventions and policies aimed at effectively curtailing HIV transmission from mother to child in this population. By addressing the unique challenges experienced by migrant mothers and their infants, this endeavor not only enhances the health outcomes and well-being of Dongguan's migrant population but also contributes significantly to broader efforts in controlling the spread of HIV. Our research introduces a distinctive perspective within the extensively examined domain of Prevention of Mother-to-Child Transmission (PMTCT) programs. In particular, we concentrate on the internally migrant Chinese population, an understudied demographic group in this context. This study, conducted in Dongguan, China, represents one of the pioneering investigations into pregnant women with HIV and their infants within this migrant community. Methods: This cross-sectional study aimed to investigate mother-to-child HIV transmission among pregnant women and neonates (≤12 months) in Dongguan People's Hospital from January 1, 2018, to December 31, 2021. Data on sociodemographic, HIV testing and treatment, and neonatal clinical details were collected using standardized forms. Chi-square and logistic regression analyses were conducted to assess associations. Results: Among 98 participants, age, marital status, and educational background showed no significant association. Similarly, the status of sexual partner, spousal therapy, and number of children had no significant impact. However, treatment strategies for positive women and the starting point of antiretroviral therapy for women with HIV were associated with transmission (P<0.05). Additionally, type of feeding, antiretroviral prophylaxis for neonates, and preventive treatment strategies showed significant associations. The preventive treatment program for neonates demonstrated no significant association.